ASSOCIATION OF SERUM URIC ACID LEVELS AND ATHEROMATOSIS OF CAROTID ARTERIES IN HYPERTENSIVE PATIENTS. (June 2022) - Papavasileiou, M.V.; Doumas, M.; Karamanou, A.; Moustakas, G.; Patsianis, S.; Aravantinos, D.; Pittaras, A.
Abstract : Objective: The aim of this study was to investigate a possible association between the serum uric acid levels with the atheromatosis of the carotid arteries of hypertensive patients and the possible role of fibrinogen in this status. Design and method: We studied 1296 hypertensive patients (45, 2% female), treated or newly diagnosed untreated, of mean age: 60, 2 ± 5, 3 years, without any known cardiovascular disease and with mean office systolic/diastolic arterial blood pressure (S/DBPo): 145, 9 ± 12.6/89.7 ± 5, 3 mmHg, mean office heart rate (HRo): 74, 3 ± 9, 9 bpm, average body mass index (BMI): 28.3 ± 5, 3 kg/m 2 and average waist circumference (WC) 96.1 ± 12.9 cm. The levels of serum uric acid (SUA), fibrinogen, urea and creatinine, were recorded. eGFR was calculated according Cockcroft-Gault Equation. All studied patients underwent triplex –Doppler ultrasound of carotids and intima -media thickness was measured (IMT) and the presence or not of atheromatous plaque was investigated. The study population was separated in two groups, according the IMT value and the existence or not of atheromatous plaque. Group A: IMT > 0.9 mm or/and existence of atheromatous plaque Group B: IMT < 0.9 mm and without any atheromatous plaque (t-test between the two groups p < = 0.001). By using the ANOVA statistic method we registered the SUA levels values in both groups as well as fibrinogen levels. Using Pearson correlation method we correlated SUA with fibrinogen serum levels Results: Table 1: Differences of serum uric acid levels between group A and group B Table 2. Correlation between serum uric acid levels with fibrinogen levels SUA: serum uric acid Conclusions: In hypertensive patients treated or not, the existence of increased thickness or atheromatous plaques in carotids was associated with significantly higher serum uric acid levels and fibrinogen levels, possibly indicating their importance in the atheromatous status of hypertensive patients while a significant positive correlation exists between SUA and fibrinogen levels in this population